2022
DOI: 10.3389/fcvm.2022.940035
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia is associated with a higher risk of mortality and arrhythmias in ST-elevation myocardial infarction, irrespective of diabetes

Abstract: AimsWe aimed to assess the impact of hypoglycemia in ST-elevation myocardial infarction (STEMI).BackgroundHypoglycemia increases the risk of mortality in patients with diabetes and high cardiovascular risk.MethodsWe used the National Inpatient Sample (2005–2017) database to identify adult patients with STEMI as the primary diagnosis. The secondary diagnosis was hypoglycemia. We compared cardiovascular and socio-economic outcomes between STEMI patients with and without hypoglycemia and assessed temporal trends.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…Furthermore, it is necessary to reasonably control the patients' blood glucose levels after the operation. Low blood glucose levels were found to be correlated with poor cardiovascular prognosis of CAD patients [21,22] . Following cardiac surgery, appropriate blood glucose level control (7.8-10.0 mmol/L) could help improve clinical outcomes [23,24] .…”
Section: Incomplete Vascularization and Graft Lesions Are Common Caus...mentioning
confidence: 94%
“…Furthermore, it is necessary to reasonably control the patients' blood glucose levels after the operation. Low blood glucose levels were found to be correlated with poor cardiovascular prognosis of CAD patients [21,22] . Following cardiac surgery, appropriate blood glucose level control (7.8-10.0 mmol/L) could help improve clinical outcomes [23,24] .…”
Section: Incomplete Vascularization and Graft Lesions Are Common Caus...mentioning
confidence: 94%
“…Moreover, hypoglycemia is independently associated with cardio and cerebrovascular events independent of insulin treatment. [105][106][107][108]…”
Section: Down-regulated Proteins -Mild Hypoglycemiamentioning
confidence: 99%
“…As hypoglycemia is de ned as blood sugar of 3.9 mmol/L or less and previous studies have found that hypoglycemia is associated with a higher risk of mortality in non-diabetic STEMI patients [10] . Thus, the relationship between ABG and MACE was analyzed again after excluding patients with ABG less than 4 mmol/L (n=34).…”
Section: Sensitivity Analysis--after Excluding Patients With Abg Less...mentioning
confidence: 99%